Fat embolism syndrome in Duchenne muscular dystrophy: report on a novel case and systematic literature review - Specht, Sabine; Zhukova, Irina; Westhoff, Jens; Erb, Larissa Diana; Ziegler, Andreas; Kölker, Stefan; Hoffmann, Georg F.; Hagmann, Sébastien; Syrbe, Steffen (European journal of paediatric neurology, 2024)
We report a non-ambulatory 13-year-old boy with Duchenne muscular dystrophy who experienced severe acute respiratory distress syndrome and cerebral fat embolism following elective soft tissue surgery. Post-surgery radiological examination revealed bilateral femoral fractures and marked osteopenia that were believed to have caused disseminated pulmonary and cerebral fat embolism. The patient had never been on glucocorticoid treatment. Five months post-surgery, he remained in a state of minimal consciousness. A literature review was performed and eleven publications included, providing case reports of a total number of 23 patients with Duchenne muscular dystrophy with fat embolism syndrome. The most common causes were falls from the wheelchair that predominantly resulted in femoral fractures. Median age at the event was around 14 years. Seven patients succumbed to complications of fat embolism. No event was described in the context of surgery. We want to raise awareness that spontaneous unnoticed fractures may occur especially in adolescents with DMD from traumatic injury of large bones and also during elective surgery with a high risk of causing fat embolism with severe sequelae.
Online verfügbar: 6. Dezember 2023, Artikelversion: 13. Dezember 2023
Gesehen am 23.02.2024